Islamic Religious Education and Social Environment as Alternative Solutions to Address Moral Degradation Resulting from Promiscuity Among Generation Z Students at SMP Negeri 1 Prigen, Pasuruan - Afwa Elfira Zulfa; Emi Lilawati; Waslah Waslah; Mohammad Saat Ibnu Waqfin; Atika Nailah Syirva (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2026)
The decline in moral values among Generation Z adolescents has become an increasingly serious concern amid the wave of digitalization. This study aims to analyze the influence of Islamic Religious Education and the social environment on mitigating the moral decline among Generation Z students at SMP Negeri 1 Prigen, Pasuruan. A quantitative approach using a survey method was employed in this study, involving 54 eighth-grade students selected through random sampling. Data collection was conducted through the distribution of a Google Forms-based questionnaire, while data analysis utilized multiple linear regression with the aid of IBM SPSS Statistics 25. The results indicate that Islamic Religious Education has a significant influence in curbing the decline in student morality, as evidenced by the reinforcement of the values of discipline, honesty, and self-control. Similarly, the social environment, whether at school, within the family, or in the community, was found to play a crucial role as a space for the internalization of moral values through daily interactions. Collectively, these two variables contributed 55.7% to mitigating moral decline, while the remainder was influenced by other factors beyond the scope of this study. These findings confirm that Islamic Religious Education and a supportive social environment are two complementary pillars in shaping the moral character of Generation Z students. Implicitly, strengthening formal religious education must be accompanied by the creation of a conducive social environment, whether at school, within the family, or in the community.